Modification of pfap2μ and pfubp1 Markedly Reduces Ring-Stage Susceptibility of Plasmodium falciparum to Artemisinin In Vitro - Henrici, Ryan C. (Antimicrob Agents Chemother, 2019)
Management of uncomplicated malaria worldwide is threatened by the emergence in Asia of Plasmodium falciparum carrying variants of the pfk13 locus and exhibiting reduced susceptibility to artemisinin. Mutations in two other genes, ubp1 and ap2μ, are associated with artemisinin resistance in rodent malaria and with clinical failure of combination therapy in African malaria patients. Transgenic P. falciparum clones, each carrying orthologues of mutations in pfap2μ and pfubp1 associated with artemisinin resistance in Plasmodium chabaudi, were derived by Cas9 gene editing. Susceptibility to artemisinin and other antimalarial drugs was determined. Following exposure to 700 nM dihydroartemisinin in the ring-stage survival assay, we found strong evidence that transgenic parasites expressing the I592T variant (11% survival), but not the S160N variant (1% survival), of the AP2μ adaptin subunit were significantly less susceptible than the parental wild-type parasite population. The V3275F variant of UBP1, but not the V3306F variant, also displayed reduced susceptibility to dihydroartemisinin (8.5% survival versus 0.5% survival). AP2μ and UBP1 variants did not elicit reduced susceptibility to 48 h of exposure to artemisinin or to other antimalarial drugs. Therefore, variants of the AP2 adaptor complex μ-subunit and of the ubiquitin hydrolase UBP1 reduce in vitro artemisinin susceptibility at the early ring stage in P. falciparum. These findings confirm the existence of multiple pathways to perturbation of either the mode of action of artemisinin, the parasite’s adaptive mechanisms of resistance, or both. The cellular role of UBP1 and AP2μ in Plasmodium parasites should now be elucidated.